Lexical Facility Size, Recognition Speed and Consistency as Dimensions of Second Language Vocabulary Knowledge - Harrington, Michael (Palgrave Macmillan UK, 2018)
This book examines the simultaneous contribution of learner vocabulary size and speed to second language performance differences across learner levels and settings. Harrington considers vocabulary size and speed, as reflected in retrieval speed and consistency, as a three-dimensional measurement construct termed lexical facility. While size and retrieval speed are generally known, this is the first attempt to incorporate consistency, as measured by the coefficient of variation, as an index of vocabulary skill. Part 1 describes the three dimensions and the roles they play on lower level text processing and thus on second language performance more generally. Part 2 reports on seven studies and related research that investigate the sensitivity of the three dimensions, both individually and in combination, to proficiency differences in common domains of academic English performance. Harrington's framework and the theoretical and methodological issues that arise are presented in a manner accessible to a wide readership, including second language acquisition vocabulary researchers, testing and assessment practitioners, and those interested in second language research methodology. Michael Harring ton teaches in the postgraduate program in Applied Linguistics at the University of Queensland, Australia. He publishes in second language acquisition, second language lexical and cognitive processes, and testing and assessment. .